Multi-modal virtual reality system for tinnitus treatment methods and validation - Hojun Aan; Kang Hyeon Lim; Jihoo Kim; Hong Jin Kim; Ye Hwan Lee; Eunjin Kim; Yoon Chan Rah; Intae Hwang; Euijin Kim; Sungkean Kim; Jimmon Kim; Jiake Yang; et al. (PLoS ONE, 2025)
Virtual reality (VR) has been utilized in clinical treatment because it can efficiently simulate situations that are difficult to control in the real world. In this study, we evaluated the efficacy of VR in patients with chronic subjective tinnitus. We assessed the clinical effectiveness based on electroencephalogram (EEG) analysis and questionnaire responses after patients participated in a 6–8-week VR-based tinnitus relief program. The intervention involved removing tinnitus avatars in the VR, through which we expected the patients to experience subjective tinnitus control. Standardized low-resolution brain electromagnetic tomography was used to analyze changes in source activity in prefrontal regions associated with tinnitus. The study included patients aged 27–68 years with chronic non-pulsatile tinnitus lasting ≥3 months. Patients completed VR sessions, neurological EEGs, and questionnaires. Statistically significant differences were observed in the tinnitus handicap questionnaire total scores immediately after treatment (p = 0.002) and 1-month post-treatment (p = 0.001) compared to those before treatment. Significant changes were also found in the visual numeric scale and profile of mood states scores 1-month post-treatment. Additionally, significant changes were observed in sensor-level and source-level power spectrum criteria immediately following the VR experiment, suggesting that similar to some forms of cognitive behavioral therapy, VR-based programs may help alleviate tinnitus-related distress in patients with chronic subjective tinnitus.